Pendapatan, Religiusitas dan Trust: Efektivitasnya Terhadap Minat Membayar Zakat Profesi Pada Lembaga Amil Zakat Harapan Dhuafa (LAZ HARFA) - Syihabudin Syihabudin; Najmudin Najmudin (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to determine (1). Effect of income on interest in paying professional zakat at LAZ HARFA. (2). The influence of religiosity on interest in paying professional zakat at LAZ HARFA. (3) The effect of trust on interest in paying zakat at LAZ HARFA. and (4). The effect of income, religiosity and trust on interest in paying zakat at LAZ HARFA. The object of this research is the employees who work in the industry in the Cikande Halal Industrial Estate. The research method used is a quantitative method. Data collection techniques using a questionnaire. The data were analyzed using multiple linear regression method through SPSS version 23 program. The results of this study indicate that (1). Income has a positive and significant effect on interest in paying professional zakat at LAZ HARFA. (2). Religiosity has a significant effect on the interest in paying professional zakat at LAZ HARFA. (3). Trust has an effect on interest in paying zakat at LAZ HARFA. (4). Income, religiosity and trust simultaneously have a positive and significant effect on interest in paying professional zakat at LAZ HARFA. The total contribution of income, religiosity and trust to interest in paying professional zakat at LAZ HARFA is 53.9 percent, while the rest is influenced by other variables not examined in this study.